2011
DOI: 10.1111/j.1365-2842.2011.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of implant‐CAD/CAM abutment connections of two different internal connection systems

Abstract: Titanium or zirconium computer-aided design/computer-aided manufacturing abutments are now widely used for aesthetic implant treatments; however, information regarding microscopic structural differences that may influence the biological and mechanical outcomes of different implant systems is limited. Therefore, the characteristics of different connection systems were investigated. Optical microscopic observation and scanning electron microscopy showed different characteristics of two internal systems, namely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…The internal conical type provides stability through contact between the implant and abutment, which enables a more favorable transmission of force and enhanced resistance to horizontal and oblique forces (Bordin et al, ; Bozkaya & Müftü, ; Machado, Bonfante, Anchieta, Yamaguchi, & Coelho, ; Merz et al, ). However, we found no significant differences between the 2 types of connections, which are similar results to previous experimental outcomes (Sumi et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The internal conical type provides stability through contact between the implant and abutment, which enables a more favorable transmission of force and enhanced resistance to horizontal and oblique forces (Bordin et al, ; Bozkaya & Müftü, ; Machado, Bonfante, Anchieta, Yamaguchi, & Coelho, ; Merz et al, ). However, we found no significant differences between the 2 types of connections, which are similar results to previous experimental outcomes (Sumi et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Compared to external or internal butt joints, conical implantabutment connections exhibit better continuity in yield forces 16,17 and possess high rigidity with low risk for leakage. 18,19 Nevertheless, internal conical connection may present mechanical disadvantages because of the reduced coronal wall thickness of the implant and may therefore have a decreased bearing capacity. 20,21 However, there is no clinical evidence comparing IL and AL setups for screw-retained restoration in implants with conical connection.…”
mentioning
confidence: 99%
“…Even though some authors have reported that this abutment was clinically acceptable, a careful inspection is required, because combinations of abutments and implants from different manufacturers can result in a misfit at the implantabutment interface. [8][9][10][11][12][13][14][15][16][17] SUMMARY Duplication of the ISIP facilitates the patient's adaptation to the ISDP. Improving the intraoral scanner and CAD program are necessary to simplify the digital workflow.…”
Section: Discussionmentioning
confidence: 99%
“…With computer-aided design/computer-aided manufacturing (CAD/CAM) technology, a customized abutment can also be applied to control the emergence profile. [8][9][10][11][12][13][14][15][16][17] Digital impression has become possible with the development of intraoral scanner systems. 1,[18][19][20][21][22] Recently, Joda et al 21 and Hinds 22 introduced digital impression techniques using a customized scannable impression coping to transfer the supraimplant soft tissue outline.…”
mentioning
confidence: 99%